Two Extracellular Poly(ε-caprolactone)-Degrading Enzymes From Pseudomonas hydrolytica sp. DSWY01T: Purification, Characterization, and Gene Analysis - Li, Linying; Lin, Xiumei; Bao, Jianfeng; Xia, Hongmei; Li, Fan (Frontiers in Bioengineering and Biotechnology, 2022)
Poly(ε-caprolactone) (PCL) is an artificial polyester with commercially promising application. In this study, two novel PCL-degrading enzymes named PCLase I and PCLase II were purified to homogeneity from the culture supernatant of an effective polyester-degrading bacterium, Pseudomonas hydrolytica sp. DSWY01T. The molecular masses of PCLase I and PCLase II were determined to be 27.5 kDa and 30.0kDa, respectively. The optimum temperatures for the enzyme activities were 50 ℃ and 40 ℃, and the optimum pH values were 9.0 and 10.0, respectively. The two enzymes exhibited different physical and chemical properties, but both enzymes could degrade PCL substrates into monomers and oligomers. Weight loss detection and scanning electron microscopy revealed that PCLase I had more effective degradation ability than PCLase II. The genes of the two enzymes were cloned on the basis of the peptide fingerprint analysis results. The sequence analysis and substrate specificity analysis results showed that PCLase I and PCLase II were cutinase and lipase, respectively. Interface activation experiment also confirmed this conclusion. Structural analysis and modeling were further performed to obtain possible insights on the mechanism.